The mediating effect of message credibility on media use and perception of fake news among students - Ahmed Elyass Hussain, Souhaila; Kilagwa, Rehema Twahiry; Mohd Zaali, Yusnita; Wok, Saodah (2018)
The issue of fake news is a major concern at the local and global levels. Dozens of news articles worldwide have reported on the spread of fake news in the political, social, economic and entertainment arenas. Malaysia, similarly, has been vigorously covering the proliferation of fake news in the media for the past few weeks. It has reached a point that a Fake News Bill was passed in Parliament, at record time, in the hope of attaining preventive measures to counter the spread of fake news. As such, this study aims to determine students’ perception of fake news in the context of their media usage and message credibility. Specifically, it aims to test the differences between traditional and social media usage among students; to determine the relationship between media use, message credibility and perception of fake news; and to analyse the mediating effect of message credibility on media use and the perception of fake news. This study tests the applicability of the Media Dependency Theory. It employs a quantitative research design using the survey method with questionnaire as its instrument for data collection. A total of 237 students from the Department of Communication, International Islamic University Malaysia (IIUM) participated in the study. Findings show that more students use social media as opposed to the traditional media. The findings also report that there are significant relationships among media use, message credibility and fake news. Message credibility mediates the relationship between media use and perception of fake news. The Media Dependency Theory is supported in this study.